Religiousness, meaning, and quality of life: Test of a mediational model among adults seeking a spiritually integrated inpatient program. Issue 4 (17th December 2020) - Hinkel, Hannah M.; Isaak, Steven L.; Abernethy, Alexis D.; Witvliet, Charlotte V. O.; Schnitker, Sarah A.; Root Luna, Lindsey M.; Currier, Joseph M.
Abstract: Objective: Religious beliefs and practices may augment a sense of meaning in life that could support quality of life (QOL) in physical, social, and emotional domains amid mental health crises. However, these associations have not been thoroughly tested among persons with serious mental illness (SMI). Methods: Focusing on 248 adults who had recently enrolled in a spiritually integrated acute psychiatric hospitalization program, we incorporated structural equation modeling to examine whether (1) religiousness would be associated with better overall QOL; and (2) inpatients' sense of meaning in life would at least partially account for the religiousness‐QOL link. Results: Religiousness was linked indirectly with QOL at the time of admission: religiousness was associated with greater meaning in life, and a higher degree of meaning in life was associated with QOL. Conclusions: Findings underscore the crucial role of religiousness for meaning and wellness among many individuals with SMI who seek stabilization and healing.